POTENTIALITY OF PETROLEUM ETHER (60-80) °C EXTRACT OF GLYCYRRHIZA GLABRA ON ANDROGENIC ALOPECIA - SUKIRTI, UPADHYAY; VIJENDER, SINGH (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objective Glycyrrhiza glabra is well known herb in Indian and Chinese traditional medicines.In our previous study it shows hair grwth promoting property in female rats so here experiments were performed for evaluating its effects in androgenic alopecia in males. Method In present study alopecia is induced in three groups(each contain six animals) of male wistar albino rats by intramuscular dose(0.1mL) of testosterone .One group was rendered devoid of any other treatment while other two groups animals are treated with finasteride and petroleum ether extract of G. glabra root topically once daily. The animals were observed during treatment period of 21 days then one animal from each group was euthanized for histoarchitecture study. Results and discussion The study revealed that petroleum ether and finasteride treated animals do not developed alopecia while alopecia was observed in only testosterone treated animals. Conclusion Thus it is concluded from this study that petroleum ether extract of G. glabra posses anti androgenic alopecia activity which is comparable to that of standard drug finasteride.